Pharmacist‐led interventions to improve medication adherence in older adults: A meta‐analysis. Issue 11 (20th July 2021) - Marcum, Zachary A.; Jiang, Shangqing; Bacci, Jennifer L.; Ruppar, Todd M.
Abstract: Background/objective: As pharmacists work to ensure reimbursement for chronic disease management services on the national level, evidence of their impact on important health metrics, such as medication adherence, is needed. However, summative evidence is lacking on the effectiveness of pharmacists to improve medication adherence in older adults. The objective was to assess the effectiveness of pharmacist‐led interventions on medication adherence in older adults (65+ years). Design/setting/participants: Using a systematic review and meta‐analytic approach, a comprehensive search of publications in PubMed, Scopus, CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Google Scholar was conducted through April 2, 2020 for randomized clinical trials of pharmacist‐led interventions to improve medication adherence in older adults. A standardized mean difference effect size (Cohen's d ) was calculated for medication adherence in each study. Study effect sizes were pooled using a random‐effects model, with effect sizes weighted by inverse of its total variance. Measurements: Medication adherence using any method of measurement. Results: Among 40 unique randomized trials of pharmacist‐led interventions with data from 8822 unique patients (mean age, range: 65–85 years), the mean effect size was 0.57 ( k  = 40; 95% Confidence Interval [CI]: 0.38–0.76). When two outlier studies were excluded from the analysis, the mean effect size reduced to 0.41 ( k  = 38; 95% CI: 0.27–0.54). A sensitivity analysis of medication adherence outcome by time point resulted in a mean effect size of 0.64 at 3 months ( k  = 12; 95% CI: 0.32–0.97), 0.30 at 6 months ( k  = 13; 95% CI: 0.11–0.48), 0.22 at 12 months ( k  = 12; 95% CI: 0.08–0.37), and 0.36 for outcome time points beyond 12 months ( k  = 5; 95% CI: 0.02–0.70). Conclusion: This meta‐analysis found a significant improvement in medication adherence among older adults receiving pharmacist‐led interventions. Implementation of pharmacist‐led interventions supported by Medicare reimbursement could ensure older adults' access to effective medication adherence support.